Secondary cancers after carbon‐ion radiotherapy and photon beam radiotherapy for uterine cervical cancer: A comparative study. (23rd March 2022) - Nitta, Yuki; Murata, Hiroto; Okonogi, Noriyuki; Murata, Kazutoshi; Wakatsuki, Masaru; Karasawa, Kumiko; Kato, Shingo; Yamada, Shigeru; Nakano, Takashi; Tsuji, Hiroshi
Abstract: Background: There are limited studies on the risk of secondary cancers after carbon‐ion radiotherapy (CIRT). We assessed the incidence of secondary cancers in patients treated with CIRT for cervical cancer. We also evaluated the incidence of secondary cancers in patients who received standard photon radiotherapy (RT) throughout the same period. Methods: This retrospective study included patients with cervical cancer who underwent curative RT at our hospital. All cancers discovered for the first time after RT were classified as secondary cancers. To compare the risk of secondary cancers among cervical cancer survivors to the general population, standardized incidence ratios (SIRs) were calculated. Results: The analysis included a total of 197 and 417 patients in the CIRT and photon RT groups, respectively. The total person‐years during the observation period were 1052.4 in the CIRT group and 2481.5 in the photon RT group. The SIR for all secondary cancers was 1.1 (95% confidence interval [CI], 0.6–2.1) in the CIRT group and 1.4 (95% CI, 1.0–2.1) in the photon RT group. The 10‐year cumulative incidence of all secondary cancers was 9.5% (95% CI, 4.0–21.5) in the CIRT group and 9.4% (95% CI, 6.2–14.1) in the photon RT group. The CIRT and photon RT groups were not significantly different in incidence ( p  = 0.268). Conclusions: The incidence of secondary cancers after CIRT for cervical cancer was similar to that after photon RT. Validation of our findings after long‐term observation is warranted. Abstract : We investigated the incidence of secondary cancers in patients treated with carbon‐ion (C‐ion) radiation therapy (RT) or photon RT for cervical cancer. The incidence of secondary cancers after C‐ion RT for cervical cancer was similar to that after photon RT.